Analysis of Organizational Strategy, Business Model, and Risk Management of Contractor PT Totalindo Eka Persada Tbk in 2022 - Abdi Suvirianto Sianturi Abdi S; Bramantyo Djohanputro (JURNAL MANAJEMEN RISIKO, 2025)
This study aims to analyze the organizational strategy, business model, and risk management implementation at PT Totalindo Eka Persada Tbk, a national construction services company. The research is conducted conceptually using a qualitative, descriptive, and analytical approach, employing PESTEL, IFAS, EFAS, SFAS, and the Business Model Canvas (BMC) to map internal–external factors and formulate priority strategies integrated with a risk management system based on ISO 31000:2018. The analysis shows that political and economic factors are the primary determinants of the continuity of construction projects. Internally, the company has strengths in reputation, human resource competence, and experience in large-scale projects, but faces weaknesses in terms of project diversification and liquidity. The SFAS results indicate that the company’s main strategies include expansion of project portfolios, technological innovation, operational digitalization, and strengthening of corporate governance (GCG). Totalindo’s project-based EPC business model emphasizes efficiency, quality, innovation, and sustainability, and also serves as the basis for performance measurement and managerial compensation through a Key Performance Indicator (KPI) system. The integration of organizational strategy and risk management has been proven to strengthen the company’s competitiveness and resilience against external changes, economic fluctuations, and operational and reputational risks. Strategic recommendations include project diversification, digital transformation, human resource development, and the implementation of sustainable, green building–based projects.